. Which equation has no solution?
F. x-5(x - 4) = 2(2x + 7) + 6
G. 5(x + 1) - 3x = 5 - 2(5 – x)
H. 1-3(x + 3) = 2(3x - 4) - 9x
J. 3(x - 4) + x = 4(3 – x)
Stendsten

Respuesta :

F. x-5(x - 4) = 2(2x + 7) + 6

Multiply the first bracket by -5.

Multiply the second bracket by 2

x-5x+20= 4x+14+6

-4x+20= 4x+20

Move +4x to the other side. Sign changes from +4x to -4x

-4x-4x+20= 20

Move +20 to the right side.

-4x-4x+20= 20-20

-8x= 0

Divide by -8

-8/8x= 0/-8

x= 0

G. 5(x + 1) - 3x = 5 - 2(5 – x)

5x+5-3x= 5-10+2x

5x-3x+5= -5+2x

2x+5= -5+2x

Move +2x to the left side. Sign changes from +2x to -2x.

2x-2x+5= -5+2x-2x

2x-2x+5= -5

Move +5 to the other side.

2x-2x+5-5=-5-5

2x-2x= -10

0= -10 ( no solution)

Answer:

Answer: G. 5(x + 1) - 3x = 5 - 2(5 – x)